2020
DOI: 10.1101/2020.05.04.075036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ilaprazole and other novel prazole-based compounds that bind Tsg101 inhibit viral budding of HSV-1/2 and HIV from cells

Abstract: In many enveloped virus families, including HIV and HSV, a crucial, yet unexploited, step in the viral life cycle is releasing particles from the infected cell membranes. This release process is mediated by host ESCRT complex proteins, which is recruited by viral structural proteins and provides the mechanical means for membrane scission and subsequent viral budding. The prazole drug, tenatoprazole, was previously shown to bind to ESCRT complex member Tsg101 and quantitatively block the release of infectious H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…However, neither the dominant-negative version of these proteins nor their depletion affects HSV-1 yield [258]. Interestingly, it has been reported that proton pump inhibitors of the prazole family, by interfering with TSG101, affect not only the budding of HIV-1 but also of different enveloped viruses, EBV included [158,159], and, more recently, in a pre-print manuscript by Leis and coworkers, of HSV-1 and HSV-2 [270]. It must be noted that the drugs appear to inhibit HSV-1 transit through the nuclear membrane and not the final envelopment in the cytosol.…”
Section: The Travel Of Herpes Simplex Virus Type 1 From the Nucleus Tmentioning
confidence: 99%
“…However, neither the dominant-negative version of these proteins nor their depletion affects HSV-1 yield [258]. Interestingly, it has been reported that proton pump inhibitors of the prazole family, by interfering with TSG101, affect not only the budding of HIV-1 but also of different enveloped viruses, EBV included [158,159], and, more recently, in a pre-print manuscript by Leis and coworkers, of HSV-1 and HSV-2 [270]. It must be noted that the drugs appear to inhibit HSV-1 transit through the nuclear membrane and not the final envelopment in the cytosol.…”
Section: The Travel Of Herpes Simplex Virus Type 1 From the Nucleus Tmentioning
confidence: 99%